You are here : a novel - Nicholls, David, 1966- (Harper, an imprint of HarperCollinsPublishers, 2024)
When a persistent mutual friend and some very unpredictable weather conspire to toss Michael and Marnie together on the most epic of 10-day hikes, neither of them can think of anything worse, until, of course, they discover exactly what they've been looking for.